The science of flavonoids - Grotewold, Erich. (Springer, 2006)
Despite the historical significance of flavonoids and their pigments in establishing the basis for modern genetics, research in this large group of secondary metabolites continues to be more intense than ever. With an impressive knowledge already available on the chemistry and the biosynthesis of flavonoids, the past few years have witnessed increasing research in the applications of flavonoids as nutraceuticals and pharmaceuticals, as well as on their roles as signal molecules within plants and between plants and other organisms. This book provides a comprehensive overview of the flavonoid field since 1990, when the last major volume on flavonoids was published. This book covers the emerging areas in the field of flavonoid research and their applications. Chemistry, biochemistry, genetics, cellular and molecular biology are combined in each chapter to tackle what are perceived to be some of the most significant challenges currently being pursued in the area of the biology of flavonoids. The stereochemistry of flavonoids -- Isolation and identification of flavonoids -- The biosynthesis of flavonoids -- The regulation of flavonoid biosynthesis -- Transport of flavonoids: from cytosolic synthesis to vacuolar accumulation -- Flavonoid pigments as tools in molecular genetics -- The evolution of flavonoids and their genes -- Flavonoids as nutraceuticals -- Flavonoids as signal molecules: targets of flavonoid action.